Small Punch Test: A Non Destructive Technique for Mechanical Characterization of Structural Steels - Pathak, K. K.; Dwivedi, K. K.; Ramadasan, E.; Balakrishnan, K. (Journal of Structural Engineering, 2025)
Important structures like steel bridges, towers, power plants may be nuclear, thermal or hydroelectric etc. use large amount of steels of varying grades. As these structures have to function under hostile environment, aging of these materials is inevitable. In order to assess the strength of aged material during the service life, miniature testing methods have become a powerful tool of structural engineers. These techniques involve use of small size samples tested by bending or shearing to fracture in a specially designed die and punch assembly. Numerical simulation of the deformation process of the miniature specimen will enable in reducing the number of experimental try outs using different geometrical, material and process parameters in short span of time. Finite element simulations of deformation process have gained wide popularity in recent years due to its various advantages. Finite element studies of the miniature tests are required to establish the material deformation details during the test and to correlate the measurements made on the disc to the uni-axial tensile properties and fracture toughness. In this study it is shown that load displacement curves obtained using experimental and simulation techniques are quite close. Hence the gamut of the characterization is to obtain the material parameters for which simulated load stroke curves matches with its experimental counterpart. It can be observed that proposed techniques are quite promising for those circumstances where only a small amount of material is available for testing purposes.